FORMULAÇÃO DE PROBLEMAS NAS AULAS DE MATEMÁTICA: O OLHAR DE UMA PROFESSORA, SEUS ALUNOS E NOVOS APRENDIZADOS - Ribeiro Rodrigues Gaioti, Lidiane; Oliveira Altoé, Renan (LINKSCIENCEPLACE, 2026)
This work is about the "Problem Posing in Mathematics" and is the result of an experience developed in the stage of regency of the Supervised Stage III, of the Superior Course of Mathematics Degree, of the Federal Institute of Espírito Santo, Cachoeiro de Itapemirim campus. She researched a teacher’s knowledge about problem posing and how her students understood it. It is a field research of a qualitative nature, developed in a State School of the municipality of Cachoeiro de Itapemirim, in the first grade of high school, and the data were produced through interviews, observations and written records of the students and analyzed in the light of the theoretical references. We conclude that the teacher knew the problem posing and learned, even more, about this practice, leading to believe in their importance in mathematics classes. The students understood it as an interesting and different practice, enabling them to discuss the content they were learning.